PRZECIĘTNY KOWALSKI. UWAGI O KONOTACJACH I MEDIALNYCH WYSTĄPIENIACH JEDNOSTKI ONIMICZNEJ - Rutkowski, Mariusz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The surname Kowalski is stable fixed both in Polish language and culture as a stereotypical Polish surname. Consequently, it is a carrier of the linguistic connotations. In this paper, the examples of its usage in the medial texts, as well as profiles, that may be disclosed in these texts. Within the most general connotation ‘ordinary Pole; common, average man’ some more detailed profiles are distinguished. All citations are taken from the National Corpus of Polish Language.